TAMING THE MONSTER OF MICRO CORRUPTION IN THE PUBLIC SERVICE OF NIGERIA: CLEANING THE AUGEAN STABLES (IUS LAW Journal, 2025)
Nigeria, the acclaimed giant of Africa is naturally and heavily endowed with immensurable resources which include solid and liquid mineral resources, land and high population. Nigeria is a leading crude oil producer both in Africa and the world at large. Many developed and industrialized nations are not naturally endowed like Nigeria but unfortunately, the country is regarded as the poverty capital of the world. This regrettable status is attributable to the impact of the menace of corruption on the economy which is sucking and drinking the health of Nigeria because where corruption thrives, poverty and not prosperity thrives. Nigeria is stigmatized on account of corruption even at the international level. The Nigerian government has enacted some anti-corruption laws and established some anti-corruption agencies but the monster is still very strong because it has pervaded every fabric of the Nigerian society including the private and public sectors. In the public service, there is hardly any office where corruption is nonexistent in Nigeria. Given the widespread of the virus of corruption in Nigeria, although it is possible to win the battle against it when appropriate measures are taken; its complete eradication would be like cleaning the Augean stable. Consequently, this article sets out to examine corruption in Nigeria vis-à-vis the fight against it which seems non-holistic. The doctrinal methodology is adopted through the study of statutory provisions etcetera from where some inadequacies were identified and recommendations which if implemented would force corruption on its kneel were offered.
Keywords: Augean Stables, Correlates, Corruption, Macro, Micro, Public